PNLDC1 is essential for piRNA 3′ end trimming and transposon silencing during spermatogenesis in mice - Deqiang Ding (Nature Portfolio, 2017)
piRNAs are regulatory RNAs that play a critical role in transposon silencing and gametogenesis. Here, the authors provide evidence that mammalian PNLDC1 is a regulator of piRNA biogenesis, transposon silencing and spermatogenesis, protecting the germline genome in mice.